Short-term forecasting of Japanese tourist inflow to South Korea using Google trends data. Issue 3 (24th March 2017) - Park, Sangkon; Lee, Jungmin; Song, Wonho
ABSTRACT: We utilize the Internet search data from Google Trends to provide short-term forecasts for the inflow of Japanese tourists to South Korea. We construct the Google variable in a systematic way by combining keywords to minimize mean squared or mean absolute forecasting errors. We augment the Google variable to the standard time-series forecasting models and compare their forecasting accuracies. We find that Google-augmented models perform much better than the standard time-series models in terms of short-term forecasting accuracy. In particular, Google models show better out-of-sample forecasting performance than in-sample forecasting.